2017
DOI: 10.1016/j.abb.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Applications of NMR to membrane proteins

Abstract: Membrane proteins present a challenge for structural biology. In this article, we review some of the recent developments that advance the application of NMR to membrane proteins, with emphasis on structural studies in detergent-free, lipid bilayer samples that resemble the native environment. NMR spectroscopy is not only ideally suited for structure determination of membrane proteins in hydrated lipid bilayer membranes, but also highly complementary to the other principal techniques based on X-ray and electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 183 publications
0
45
0
Order By: Relevance
“…Nanodiscs can be also used to analyze oligomer state or interaction with other membrane proteins (Boldog et al 2006;Shih et al 2005). Nanodiscs can be handled like soluble molecules and are effectively used for both solution NMR (Hagn and Wagner 2015;) and solid state NMR Opella and Marassi 2017) in addition to EM studies.…”
Section: Membrane Protein Assembly Into Nanodiscsmentioning
confidence: 99%
“…Nanodiscs can be also used to analyze oligomer state or interaction with other membrane proteins (Boldog et al 2006;Shih et al 2005). Nanodiscs can be handled like soluble molecules and are effectively used for both solution NMR (Hagn and Wagner 2015;) and solid state NMR Opella and Marassi 2017) in addition to EM studies.…”
Section: Membrane Protein Assembly Into Nanodiscsmentioning
confidence: 99%
“…In globular proteins, it has been found that magic-angle spinning SSNMR can resolve complete protein structures [11][12][13][14][15][16]. This has been adapted to membrane proteins, which are more challenging due to lower sensitivity, spectral degeneracy, and complicated sample preparation [4,6,7,[17][18][19][20][21]. Structures solved using this technique include those of the microbial photosensor Anabaena sensory rhodopsin [22], chemokine receptor CXCR1 [23], Influenza A M2 channel [24], transmembrane protein CrgA from Mycobacterium tuberculosis [25], and outer membrane protein G [26].…”
Section: Introductionmentioning
confidence: 99%
“…The robust expression of milligram quantities of a structurally homogeneous protein and its functional reconstitution into a membrane-like environment are the key requirements for the successful structural and dynamic SSNMR analysis of a membrane protein [20,21,44,45]. Heterologous expression of eukaryotic membrane proteins can be especially challenging due to intrinsic low expression levels as well as native-folding and post-translational modifications that are often not supported by the E. coli expression system [39,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…13 C, 15 N). NMR signals can be measured in solution, ambient temperature, and otherwise native-like conditions, including for membrane proteins [42]. Protocols for NMR isotope labeling are readily available in bacterial, yeast, insect, and mammalian expression systems [43–45], though the latter two can be economically prohibitive, given the relatively high concentrations of pure protein (typically 500 ÎŒL of a ≄ 150 ÎŒM solution) required.…”
Section: Introductionmentioning
confidence: 99%